Practices and Mechanisms of Cross-Country Arrests Against Criminals - Pradantya Adi Wibawa, Anak Agung Gde (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The procedure of law enforcement against international crime includes the problem of developing bilateral and multilateral cooperation in preventing and combating international criminal acts. For example, by entering into an extradition agreement or by entering into a Mutual Legal Assistance (MLA) agreement. Both have different understandings where extradition can be interpreted as a formal surrender made either on the basis of a pre-existing extradition treaty or based on the principle of reciprocity or good relations, for someone accused of a crime (suspect, accused, accused) or someone who have been sentenced to criminal penalties that have definite binding powers (convicted and convicted), whereas Mutual Legal Assistance are agreements between two foreign countries for information purposes and information exchange in an effort to enforce criminal law. Very interesting from this research will be discussed later about the Practice of Cross-border Arrest in the International World, and the Practice of Cross-border Arrest in its Relationship with Indonesia using the Descriptive Normative research method, with legislation and historical approaches.